Hepatitis C Virus Core Antigen As Alternative Diagnostic Algorithm For Active Hepatitis C Virus Infection Among Haemodialysis Population: Cost Implications - Xue Z. Wong; Amirah Azzeri; Chye C. Gan; Shabaruddin Fatiha; Dahlui Maznah; Rosnawati Yahya; Shubash Ganapathy; Soek S. Tan; Rosmawati Mohamed; Soo K. Lim (John Wiley & Sons, Inc., 2024)
Indexed by ERA